Meningkatkan Keterampilan Berbicara Dengan Model Role Playing Pada Siswa Kelas V SD Negeri 1 Poka: Indonesia - Rahayaan, Ami Rahman; Ririhena, Ribka L.; Notanubun, Zainudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the speaking skills of fifth-grade students at Poka 1 Elementary School through the implementation of the Role Playing learning model. The background of the study is the low speaking skills of students, characterized by a lack of confidence, imprecise pronunciation, and minimal variation in intonation and expression. The study used the Classroom Action Research (CAR) method with two cycles. Twenty students participated. The instruments used included a speaking skills test, observation sheets, and documentation. Each cycle consisted of planning, implementation, observation, and reflection. The results showed an improvement in students' speaking skills. The average score in the pre-cycle was 62%, increasing to 69% in Cycle I and 90% in Cycle II. Improvements occurred in the aspects of topic development, intonation, pronunciation accuracy, and expression. The study concluded that the implementation of the Role Playing model effectively improved students' speaking skills. This model is recommended as an alternative strategy for learning Indonesian in elementary schools